Characterizing the Impact of Race and Contemporary Redlining on Receipt of Guideline-Concordant Locoregional Therapy Among Older Women With Breast Cancer - Sara Beltrán Ponce, MD; Bethany Canales, MPH; Emily L. McGinley, MS, MPH; Tina W.F. Yen, MD, MS; Sergey Tarima, PhD; Yuhong Zhou, PhD, MS, ME; Jean C. Bikomeye, MPH; Kirsten M.M. Beyer, PhD, MPH, MS (Advances in Radiation Oncology, 2025)
Purpose: Improving locoregional control for breast cancer (BC) results in better overall survival. Contemporary redlining is associated with worse BC survival in older patients. Self-reported race is associated with survival, redlining, and access to care. We aim to examine the relationship between race, redlining, and the receipt of guideline-concordant locoregional therapy (LRT) in older women with BC. Methods and Materials: Women aged 66 to 90 years with stage I to III BC diagnosed in 2010 to 2017 with known metropolitan statistical area were identified in Surveillance, Epidemiology, and End Results-Medicare. Redlining was estimated using Home Mortgage Disclosure Act data. Guideline-concordant LRT was assessed based on receipt of surgery and appropriate adjuvant radiation treatment. A logistic regression model was fitted to examine the relationship between redlining and receipt of guideline-concordant LRT, accounting for covariates. Cluster bootstrap at the MSA-level was used. Results: The cohort included 64,987 women: 31% aged 66 to 70, 82% non-Hispanic (NH) White, 12% with dual Medicaid/Medicare enrollment. Ninety-four percent underwent surgical resection; 84% received guideline compliant LRT. NH Black race was associated with lower receipt of guideline-concordant LRT compared to NH White (odds ratio [OR], 0.78; 95% CI, 0.71-0.84). No significant differences were noted between NH White and NH Asian or Hispanic women. Residing in high-redlining areas was associated with lower odds of receiving guideline-concordant LRT compared to low-redlining areas (OR, 0.89; 95% CI, 0.82-0.95, P = .002). Conclusions: In this cohort of older women with BC, NH Black race and redlining, even after adjusting for several important clinical and demographic factors, were associated with a lower likelihood of receiving guideline-concordant LRT. This finding demonstrates the profound impact of interpersonal racism and redlining on receipt of cancer-directed therapies and highlights the need for further work to combat systemic inequities and interpersonal racism.